Unsteady MHD mixed convection flow of a hybrid nanofluid with thermal radiation and convective boundary condition - Wahid, Nur Syahirah; Md Arifin, Norihan; Khashi’ie, Najiyah Safwa; Pop, Ioan; Bachok, Norfifah; Hafidzuddin, Mohd Ezad Hafidz (Zhonghua Minguo Wuli Xuehui, 2022)
Heat transfer enhancement is a current concern in a variety of areas. Nanofluid, a novel kind of heat transfer fluid, may be used as an efficient medium for improving heat transmission. A numerical investigation is necessary to approximate the flow properties. In this study, the flow and heat transfer of the unsteady magnetohydrodynamic mixed convective hybrid nanofluid along a permeable vertical plate is numerically elucidated. The imposition of thermal radiation and convective boundary condition is considered towards the model. A sophisticated similarity transformation is adapted to simplify the governing formulations of the model into similarity equations which then are being solved via numerical solver in Matlab. The numerical findings of this study in the absence of nanoparticles and unsteadiness effect are consistent with those analytical solutions available in the literature. Dual solutions are perceived to appear because of the opposing flow contributed by the combination of mixed convection, injection, and unsteadiness parameters. Hence, to confirm the practicality of the solutions, stability analysis is conducted, and the first solution is stable. Greater skin friction and heat transfer rate are established by only a small and reduced copper volume fraction and magnetohydrodynamic effect when the negative values of mixed convection and unsteadiness parameter are considered. Therefore, this present study suggests minimizing the hybrid nanofluid concentration and maximizing the thermal radiation to achieve a better heat transfer capability within the other considered flow effects.